2020
DOI: 10.1155/2020/8851415
|View full text |Cite
|
Sign up to set email alerts
|

Altered Functional Connectivity after Epileptic Seizure Revealed by Scalp EEG

Abstract: Epileptic seizures are considered to be a brain network dysfunction, and chronic recurrent seizures can cause severe brain damage. However, the functional brain network underlying recurrent epileptic seizures is still left unveiled. This study is aimed at exploring the differences in a related brain activity before and after chronic repetitive seizures by investigating the power spectral density (PSD), fuzzy entropy, and functional connectivity in epileptic patients. The PSD analysis revealed differences betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Focal damage in any of these regions could result in reduced abilities to activate this whole network and might thus be associated with more difficulties in all these domains. Furthermore, repeated seizures may have lasting effects on brain network activity, affecting also distant regions (Englot et al, 2015 ; Liang et al, 2020 ). It has been reported that chronic epilepsy can induce neural reorganization in adult brains (Elger et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Focal damage in any of these regions could result in reduced abilities to activate this whole network and might thus be associated with more difficulties in all these domains. Furthermore, repeated seizures may have lasting effects on brain network activity, affecting also distant regions (Englot et al, 2015 ; Liang et al, 2020 ). It has been reported that chronic epilepsy can induce neural reorganization in adult brains (Elger et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in patients with chronic epilepsy, a negative correlation has been found between clustering coefficient/local efficiency of white matter structural networks and cognitive function (Vaessen et al, 2012). Furthermore, epileptic activity can reduce long-range connectivity and enhance local connectivity in the postseizure functional connectivity compared to the preseizure functional connectivity (Liang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in patients with chronic epilepsy, a negative correlation has been found between clustering coefficient/local efficiency of white matter structural networks and cognitive function (Vaessen et al., 2012). Furthermore, epileptic activity can reduce long‐range connectivity and enhance local connectivity in the postseizure functional connectivity compared to the preseizure functional connectivity (Liang et al., 2020). As we included, in the current study, only patients using antiepileptic drugs, and some were well controlled for several months, this may also explain the absence of statistically significant differences in the global brain structural network properties between patients with hippocampal sclerosis and healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Within each segment, the power spectrum density was estimated using the Welch method in windows of 1 s, with overlap of 75% up to 40 Hz. As the literature suggests that the delta band is one of the most meaningful for seizure analysis [15], only the averaged connectivity matrices between 0.5 Hz and 4 Hz was analysed.…”
Section: B Preprocessingmentioning
confidence: 99%